Learning path : beginning UX design. - Nordin, Dani; Perfetti, Christine; Inzucchi, Nick (O'Reilly Media, 2015)
"Design rich, interactive experiences your users will love. Your audience has astonishingly high expectations when it comes to user experiences, putting the pressure on you to deliver a UX they can't resist—on whatever device they choose to use. In this Learning Path you'll acquire the skills to design multi-device experiences that enchant your users anywhere."--Resource description page.